Perceived social approval and condom use with casual partners among youth in urban Cameroon - Meekers Dominique; Van Rossem Ronan (BMC, 2011)
Abstract Background HIV prevention programs targeting youth often emphasize the role of peers, and assume that youths will model their behavior after their peers'. We challenge this view; we argue that adopting a given behavior requires social approval, and that youths do not necessarily turn to peers for such approval. This study analyzes survey data on youths in urban Cameroon to 1) identify which type of persons youths look to for social approval, and 2) establish how important social approval by these persons is for condom use among youths. Methods We analyzed data from three survey waves (2000, 2002, and 2003) of a reproductive health survey conducted among urban Cameroonian youth (aged 15-24). Only respondents who reported having at least one casual partner in the past year were retained for the analysis. Bivariate analyses and structural equation modeling were used to examine relationships among perceived social approval, attitudes towards condoms and condom use. Results The data show that only 3% of youths named their friends as people whose opinion they valued, while 93% mentioned family members. The perceived approval of condom use by these persons had a significant positive effect on the frequency of condom use among youths. The frequency of condom use was also affected by the respondents' attitudes toward condom use, the range of persons with whom they discussed reproductive health matters, whether they were enrolled in school, socioeconomic status, their self-efficacy, perceived severity of AIDS, risk perception and sexual risk behavior. The perceived social approval of condom use and the respondents' own condom attitudes were correlated. Conclusions Our analysis demonstrates that perceived social approval facilitates the adoption of condom use among urban Cameroonian youth. However, youths tend to value the opinions of family members much more than the opinions of their peers. These results suggest that interventions targeting youths should not focus exclusively on peers but should also include other groups, such as parents and community leaders.